AIR MATH

Math Question

Which shows the correct substitution of the values \( a, b \), and \( c \) from the equation \( -2=-x+x^{2}-4 \) into the quadratic formula?
Quadratic formula: \( x=\frac{-b \pm \sqrt{b^{2}-4 a c}}{2 a} \)
\( x=\frac{-(-1) \pm \sqrt{(-1)^{2}-4(1)(-4)}}{2(1)} \)
\( x=\frac{-1 \pm \sqrt{1^{2}-4(-1)(-4)}}{2(-1)} \)
\( x=\frac{-1 \pm \sqrt{(1)^{2}-4(-1)(-2)}}{2(-1)} \)
\( x=\frac{-(-1) \pm \sqrt{(-1)^{2}-4(1)(-2)}}{2(1)} \)

Solution

solution

AIR MATH homework app,
absolutely FOR FREE!

  • AI solution in just 3 seconds!
  • Free live tutor Q&As, 24/7
  • Word problems are also welcome!
appstoreplaystore

Scan the QR code below
to download AIR MATH!

qrcode